2009
DOI: 10.1038/aps.2009.45
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of compound FLZ, a novel synthetic analogue of squamosamide, on β-amyloid-induced rat brain mitochondrial dysfunction in vitro

Abstract: Aim:The aim of the present study was to assess the effects of N- [2-(4-hydroxyphenyl)ethyl]-2- (2,5-dimethoxyphenyl)-3-(3-methoxy-4-hydroxyphenyl)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 42 publications
(159 reference statements)
0
2
0
Order By: Relevance
“…The pathogenesis of AD is very complex and still not fully understood. Accumulating evidences showed that the misfolding and aggregation of Aβ can induce mitochondrial dysfunction, oxidative stress, neuronal apoptosis, hyperphosphorylated Tau protein and lead to the progressive impairment in memory and cognition, which is involved in the pathogenesis of AD 3‐5 . So, reducing Aβ deposition and neurotoxicity is considered as a significant target for anti‐AD drug research and effective clinical strategy for the prevention and treatment of AD 6,7 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pathogenesis of AD is very complex and still not fully understood. Accumulating evidences showed that the misfolding and aggregation of Aβ can induce mitochondrial dysfunction, oxidative stress, neuronal apoptosis, hyperphosphorylated Tau protein and lead to the progressive impairment in memory and cognition, which is involved in the pathogenesis of AD 3‐5 . So, reducing Aβ deposition and neurotoxicity is considered as a significant target for anti‐AD drug research and effective clinical strategy for the prevention and treatment of AD 6,7 …”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidences showed that the misfolding and aggregation of Aβ can induce mitochondrial dysfunction, oxidative stress, neuronal apoptosis, hyperphosphorylated Tau protein and lead to the progressive impairment in memory and cognition, which is involved in the pathogenesis of AD. [3][4][5] So, reducing Aβ deposition and neurotoxicity is considered as a significant target for anti-AD drug research and effective clinical strategy for the prevention and treatment of AD. 6,7 Caenorhabditis elegans (C. elegans) is a free-living, non-parasitic nematode, which has been considered as a model organism for the study of ageing and age-related diseases, including AD and Parkinson's disease.…”
mentioning
confidence: 99%